Occupational change in Britain and Germany - Simonetta Longhi; Malcolm Brynin (University of Essex, Institute for Social and Economic Research (ISER), 2009)
We use British and German panel data to analyse job changes involving a change in occupation. We assess the extent of occupational change, taking into account the possibility of measurement error in occupational codes; whether job changes within the occupation differ from occupation changes in terms of the characteristics of those making such switches; and the effects of the two kinds of moves in terms of wages and job satisfaction. We find that occupation changes differ from other job changes, generally reflecting a less satisfactory employment situation, but also that the move in both cases is positive in respect of change in wages and job satisfaction.
Keywords: 330